Marxism and History - Perry, Matt. author. aut Link
IX, 195 p. 1 illus.
Keywords: This textbook examines Marxism’s enormous impact on the way historians approach their subject. Tackling current historiographical questions in an accessible way, the author offers a clear introduction to Marxist views of history, key Marxist historians and thinkers, and the relevance of Marxist theory and history to students’ own work. This is a concise, thorough overview of an important area of historiography. The second edition incorporates significant new developments in research, including Marxist contributions to the emergence of global, maritime and transnational history; the discovery of Marx’s ecologism and the historical critique of fossil capitalism as a source of environmental disaster; a reassessment of gender oppression through social reproduction theory; and the contribution of Marxism to debates on race, Eurocentrism and whiteness. .